2006
DOI: 10.1177/1469787406064750
|View full text |Cite
|
Sign up to set email alerts
|

Service-learning

Abstract: This exploratory study conducted at a mid-sized American Midwestern metropolitan university explores service-learning. The study describes the characteristics of students choosing service-learning and examines learning from the students’ perspective. A survey instrument was used to assess the attitudes of 500 randomly selected students, some of whom participated in service-learning projects. Their responses were contrasted with students who did not participate in a service-learning opportunity. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Their open-ended responses indicated that the assistance they received on essays, on time management, on expanding their college set, and on understanding life on campus was helpful as well. In interviews, former high school students discussed the multiple options that working with the college students provided and the skills they honed or learned that were helpful when they enrolled in college (Bordelon & Phillips, 2006). Finally, every high school student, both on the survey and in interviews, reported the program was helpful as well, answering the second research question which asked how they described their experiences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Their open-ended responses indicated that the assistance they received on essays, on time management, on expanding their college set, and on understanding life on campus was helpful as well. In interviews, former high school students discussed the multiple options that working with the college students provided and the skills they honed or learned that were helpful when they enrolled in college (Bordelon & Phillips, 2006). Finally, every high school student, both on the survey and in interviews, reported the program was helpful as well, answering the second research question which asked how they described their experiences.…”
Section: Discussionmentioning
confidence: 99%
“…In interviews with the former high school students, many of these ideas were echoed, particularly expanding options for college and for majors (Bordelon & Phillips, 2006). One said, "just applying to college is pretty simple, but it was kind of scary for me."…”
Section: Former High School Student Interviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since its introduction as a promising practice in 1993 via the National and Community Service Trust Act, research shows that successful service-learning arrangements are both possible and attainable (Baldwin, Buchanan, & Rudisill, 2007; Carrington & Saggers, 2008; Muwana & Gaffney, 2011). Even so, service-learning partnerships demand significant time and consideration (Bordelon & Phillips, 2006; Bringle & Hatcher, 1996). For the purposes of this article, we utilized the National Service-Learning Clearinghouse’s (Generator School Network, 2013) definition of service-learning, which states that it is a “teaching and learning strategy that integrates meaningful community service with instruction and reflection to enrich the learning experience, teach civic responsibility, and strengthen communities.” This type of service is intended to meet community needs while offering reciprocal benefits for those providing and engaging in the service alike (Bringle & Hatcher, 1996).…”
mentioning
confidence: 99%